The Length of Use of Panty Liner with the Incidence of Vaginal Discharge in Adolescent Girls - Syamson, Meriem Meisyaroh; Ade Srywahyuny; Asnuddin; Muhammad Tahir; Wilda Rezki Pratiwi (Journal Of Nursing Practice, 2026)
Background: The phenomenon in women and adolescent girls has experienced vaginal discharge in 60% of adolescents (15-22 years old) and 40% of women (23-45 years old); if left, vaginal discharge can have bad impacts on health, one of which is cervical cancer, it was found that the main cause of cervical cancer in Indonesia is poor quality sanitary napkins. Physiological vaginal discharge usually occurs before and after menstruation, and abnormal vaginal discharge is called pathological vaginal discharge, which occurs due to an infection in the vagina. Purpose: The purpose of the study was to determine the relationship between the length of wearing panty liners and the incidence of vaginal discharge in adolescent girls. Methods: The quantitative method with the correlation analysis method and using a cross-sectional design, the research instrument used a questionnaire. The population was 95 students, and the number of samples was 79 people with purposive sampling techniques; the data were analyzed with univariate and bivariate analysis. Results: The results showed that there was a relationship between the length of wearing panty liners and the incidence of vaginal discharge in adolescent girls. The results showed that there was a significant relationship between the duration of panty liner use and the incidence of vaginal discharge among adolescent girls. A total of 44 respondents (55.7%) used panty liners in the abnormal category, while 35 respondents (44.3%) were in the normal usage category, with a p-value of 0.001 < 0.05. Conclusion: This indicates that wearing panty liners for an extended period can increase the risk of vaginal discharge in adolescent girls. It is recommended that the use of panty liners be limited and replaced periodically to prevent vaginal discharge and maintain the health of the intimate organs.